40 Retrospective analysis of Alopecia in patient receiving Proton Beam Radiotherapy in Neuro-oncology – Single centre experience - Hasti Barot; Vandana Kushwaha; Mithushanaa Nesarajah; Adila Amariyil; Karthica Indramohan; Michelle Newman; Michael Kosmin; Naomi Fersht (Neuro-Oncology, 2026)
Abstract Introduction Alopecia is a common and cosmetically distressing adverse effect of cranial irradiation that significantly affect quality of life in patients. Radiation induced alopecia can be short term or long term or can rarely be permanent. This study aims to evaluate the incidence of acute (≤90 days after completion) and long-term (>90 days) and permanent alopecia in brain tumour patients treated with proton beam therapy in our centre and to establish if the incidence or severity correlates with the scalp dose. Methods We retrospectively identified 253 adult neuro-oncology patients treated with proton beam therapy in our centre from September 2021 to September 2025. The scalp was contoured uniformly in all the patients to ensure consistent results. Dosimetric calculations were then done to look at maximum (Dmax) and mean doses (Dmean) and other volumetric parameters. Clinical alopecia data were extracted from proton outcomes flowsheets filled at baseline and in subsequent visits during and post treatment capturing of both short term and long-term alopecia and graded using CTCAE grading system. Planned analysis include establishing the incidence of alopecia, severity and correlation between radiation-induced alopecia and scalp dose. Results The data extraction and analysis are ongoing. At the time of presentation, detailed dosimetric profiles and their correlation with clinical alopecia outcomes will be reported, including identification of potential dose–response thresholds. Conclusion This study will provide real-world evidence on radiation-induced alopecia and to evaluate scalp dose–toxicity relationships following PBT in adult neuro-oncology patients. Findings may help inform dose constraints, optimise treatment planning, and support improved patient counselling regarding alopecia risk.